The potential for marrying local gastronomy and wine: The case of the 'fortunate islands' - Alonso, A.; Liu, Yi (Pergamon Press Plc, 2011)
For centuries, the Mediterranean and other regions have become icons for their food, wine, laid-back lifestyle and benign weather, with each of these components ideally complementing the other three. The availability of a local cuisine and local wines provides consumers with memorable experiences. However, in many other regions little is known about ways in which the local cuisine and wine could be ‘married.’ This study examines the views of 55 small winery operators in a region that for decades has been widely known as a mass tourism destination: the Canary Island in Spain. While most operators recognise the potential for a perfect local cuisine–wine marriage, many also mention the missing link between the local hospitality and wine sectors. For instance, respondents argue that restaurateurs are not promoting local wines enough in favour of cheaper imports. The study also discusses the implications of the findings and identifies areas of future research.